The promising inhibition of the joint embriyonic period in the cancer stem cells and notch pathway - Öktem, Gülperi; Uslu, Serap; Uysal, Ayşegül; Bilir, Ayhan; Ayla, Şule; Soner, Burak Cem; Çal, Çağ (Cerrahpaşa Medical Journal, 2014)
Objectives: The Notch signaling plays role to provide determining of cell fate and surviving of stem cell in the embryonic and postnatal development. The retardation effects of Notch in adult acts as oncogene or tumor suppressor gene. Notch 1 receptor and Notch ligands, Delta 1 and Jagged 1 interconnect with plasma membrane plays active role in duration of embryogenesis and malign diseases development. Cancer Stem Cells (CSC) are tumor cancer cells, their many characteristics are similar with stem cells. Verapamil is a calcium canal blocker which completely disappeared “Side Population” (SP) cells. If effective mechanism of Verapamil enlightened in the embryonic development, it could be guide in cancer researches for many new alternative therapies by the way of CSC. Methods: In our study, we aimed to examine possible changes in the Notch pathway of sublethal doses of Verapamil in the fetal kidney during embryogenesis. Verapamil was administrated 2x10mg/kg/day from embryonic 9th day (E9) and fetal kidneys were removed in 18th (E18) and 21th (E21). C-kit receptor tyrosine kinase (CD 117) for stem cells and Notch 1 receptor, Delta 1 and Jagged 1 ligands in the Notch pathway was determined by immunohistochemistry. Results: As a result, inhibitor effect (E21) of Verapamil in Notch pathway was significantly increased, immunoreactivity of c-kit decreased especially in glomerular and tubular areas in the metanephric kidney. Conclusion: In conclusion the effects of Verapamil in embryonic development and the correlative mechanism with CSC can be guide for the treatment of cancer and enable to new alternative therapies.